Are patients and physicians willing to accept less-radical procedures for cervical cancer? - Gungorduk, Kemal; Kocian, Roman; Basaran, Derman; Turan, Taner; Ozdemir, Aykut; Cibula, David (Journal of gynecologic oncology, 2018)
OBJECTIVE: To evaluate the opinions of women who underwent surgery for cervical cancer (CC) and physicians who treat CC about the acceptability of increased oncological risk after less-radical surgery. METHODS: One hundred eighty-two women who underwent surgery for CC and 101 physicians participated in a structured survey in 3 tertiary cancer centers in Czech Republic and Turkey. Patients and physicians were asked whether they would accept any additional oncological risks, which would be attributable to the omission of parametrectomy (radical hysterectomy/trachelectomy vs. simple hysterectomy/trachelectomy) or pelvic lymph node dissection (systematic resection vs. sentinel lymph node sampling). RESULTS: Although 52.2% of patients reported morbidity related to their previous treatment, the majority of patients would not accept less-radical surgical treatment if it was associated with any increased risk of recurrence (50%-55%, no risk; 17%-24%, risk <0.1%). Physicians tended to accept a significantly higher risk than patients in the Czech Republic, but not in Turkey. Patients with higher education levels, more advanced-stage of disease, or adverse events related to previous cancer treatment, and patients who received adjuvant therapy were significantly more likely to accept an increased oncological risk. CONCLUSION: Patients, even if they suffered from morbidity related to previous CC treatment, do not want to choose between oncological safety and a better quality of life. Physicians tend to accept the higher oncological risk associated with less-radical surgical procedures, but attitudes differ regionally. Professionals should be aware of this tendency when counselling the patients before less-radical surgery.
Keywords: senioři; Turecko; Attitude of Health Personnel; Česká republika; Risk Assessment; Middle Aged; průzkumy a dotazníky; Turkey; Neoplasm Recurrence, Local; Hysterectomy; Adult; Prospective Studies; postoj zdravotnického personálu; lokální recidiva nádoru; nádory děložního čípku; Czech Republic; Morbidity; kvalita života; Health Knowledge, Attitudes, Practice; Neoplasm Staging; ženské pohlaví; hodnocení rizik; Lymph Node Excision; Humans; prospektivní studie; Surveys and Questionnaires; Surgery; lidé středního věku; lymfadenektomie; staging nádorů; Uterine Cervical Neoplasms; hysterektomie; adjuvantní chemoterapie; dospělí; zdraví - znalosti, postoje, praxe; Female; Aged; Quality of Life; Chemotherapy, Adjuvant; lidé